The quality of the forage eaten by Norwegian reindeer on South Georgia in summer - Mathiesen, Svein D.; Aagnes Utsi, Tove H. (Rangifer, 2000)
The chemical composition and digestibility of plants selected by Norwegian reindeer (Rangifer t. tarandus) on the sub-Antarctic island of South Georgia (SG) were investigated in the austral summer and compared with two qualities of standard grasses of Phleum pratense of European origin. Paridiochola flabellata, Poa pratense, Poa annua, Deschampsia antarctka, and Phleum alpinum collected on SG contained 14.8, 17.6, 22.8, 16.1 and 10.1% respectively of crude protein of dry matter (DM). Aceana magellanica also collected on SG contained 19.8% of crude protein and 18.8% of water-soluble carbohydrates (WSC) of DM, while the tussock grass P. flabellata, contained as much as 29-3% of WSC of DM. Total plant cell-wall contents (CWC), including cellulose, hemi-cellulose and lignin in P. flabellata, P. pratense, P. annua and P. alpinum were 53.2, 49.6, 41.7 and 40.4% of DM respectively, while A. magellanica contained only 17.5% of DM CWC. The lignin concentrations of plants analysed varied between 1.2 and 3.2% of DM. Mean in vitro dry matter digestibility (IVDMD) of selected plants ranged from 70% in P. flabellata to 83% in P. alpinum after 48 h incubation in rumen fluid from these reindeer. In contrast, the IVDMD of the poor and high quality standard grass Phleum pratense were 54% and 73% of DM, respectively. The forage eaten by reindeer on SG in summer was of high quality, with low lignin content, moderate protein concentration and high degradability in rumen fluid.